Effects of Climbing Choice, Demographic, and Climate on Walking Behavior - Ekawati, Febriani Fajar; Eves, Frank Francis (Kesmas, 2020)
Walking is a public health recommendation to increase physical activity. Although walking for transport is associated with health benefits, it is frequently avoided when a mechanized alternative is available and when the weather or individuals’ available resources are unfavorable. The present quasi-experimental study used chosen walking speed to estimate the use of resources by pedestrians and investigated 730 pedestrians’ behavior when approaching a choice point between a short stair and a ramp at an exit from a university campus toward the local train station on six separate days. Results revealed that individuals who climbed the stairs walked faster than those who chose the ramp. In addition, females and those who were overweight walked slower than their comparator groups. Temperature was associated with walking behavior; as temperature increased, the walking speed of pedestrians decreased. Moreover, the purpose of walking is an important determinant of walking speed. Minimization of time to arrive at the train station as quickly as possible is a plausible alternative explanation for the effects of resource allocation on walking speed.